The Role of Open Science and Geoinformatics in Advancing Sustainable Development Goals in Africa: A Strategic Framework and an Action Plan - Rania Elsayed Ibrahim; Islam Abou El-Magd; Tshiamo Motshegwa; Hamed Abdelreheem Ead; Madara Ogot; Joseph Wafula; Abotalib Z. Abotalib; Nokuthula P. Mchunu; Sepo Hachigonta; John Kinyuru; Elham M. Ali (Data Science Journal)
Open Science (OS) encourages research accessibility, openness, reusability and reproducibility, which are all vital for the growth of the scientific community worldwide. Open data, in general, and remote sensing/geospatial data, in particular, offer significant economic and societal benefits that can be of great contribution to achieving the African Agenda 2063. This article focuses on examining the importance and contribution of OS and Geoinformatics to accomplish the African Agenda 2063 and Sustainable Development Goals (SDGs) in Africa, and how OS principles can enhance accessibility, collaboration, reproducibility, and innovation in geosciences. It also explores the potential of artificial intelligence on augmenting OS and Geoinformatics and proposes solutions to address the implementation challenges. It also evaluates the relationships, international financing, and cooperative efforts required to fully realize the potential of open research and geoinformatics in Africa compared to developed countries. The results revealed that the promotion of OS aims to make geospatial data and tools more accessible to researchers and policymakers, addressing critical challenges such as climate change and crisis management. The results highlighted the importance of international collaboration through the African Open Science Platform. By presenting a comprehensive framework and an action plan, this study offers a roadmap for African governments to leverage OS and Geoinformatics to advance Agenda-2063 and the SDGs, bridging the gap between theoretical knowledge and practical application.